5x=-70-3(2x-5)

Simple and best practice solution for 5x=-70-3(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x=-70-3(2x-5) equation:



5x=-70-3(2x-5)
We move all terms to the left:
5x-(-70-3(2x-5))=0
We calculate terms in parentheses: -(-70-3(2x-5)), so:
-70-3(2x-5)
determiningTheFunctionDomain -3(2x-5)-70
We multiply parentheses
-6x+15-70
We add all the numbers together, and all the variables
-6x-55
Back to the equation:
-(-6x-55)
We get rid of parentheses
5x+6x+55=0
We add all the numbers together, and all the variables
11x+55=0
We move all terms containing x to the left, all other terms to the right
11x=-55
x=-55/11
x=-5

See similar equations:

| 36x-8=45 | | 8-2m=12 | | 10x-5-2x=4(x+2) | | x*0.05=1500 | | 2(r-4)=6 | | 4x-x=7x2 | | x-2=-44+5x | | 0.25^x=0.84 | | 8x+.50=12x+.25 | | 6x+6=-21 | | 7x-6=4(3x+1) | | 1-c=-1 | | 4x+8*0.8=40 | | 6x-6=3x3x+3=9 | | 2x-5=5+2x | | u+12/5=9 | | 150m-100m+47,500=51,250-200m | | x/12=3/17 | | 2x-3x=1+99 | | 12u-6u=48 | | 72+8x=17x | | -50+3x=-11. | | 14.2=9(-5.8+t | | 3-4x/5=4/5+x/5 | | 13d-5d-11d=18 | | 4x=10x+24 | | 2v=-10+3 | | -9(-7x+2)=-459 | | 104x=8x1 | | 12x+4=40+6x | | t-+3=3 | | 3x+12=5x–8 |

Equations solver categories